Analisis Wacana Iklan Susu Frisian Flag: Pendekatan Teun A.Van Dijk dalam Menggali Makna Tersembunyi - Ananda Yohana Lumban Tobing; Anella Roveriana Sitanggang; Dahlia Veronika Siregar; Feffiola Destiana Margaretha Pakpahan; Marwinda Silalahi; Natasya Poronika Panggabean; Romiana Situmorang (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the Frisian Flag milk advertisement using the Critical Discourse Analysis (CDA) model by Teun A. van Dijk, which focuses on three dimensions: text structure, social cognition, and social context. Advertisements are seen not only as a means of conveying product information but also as tools that embed ideologies, cultural values, and social constructions. This research uses a literature study method combined with observation and documentation techniques on advertisements broadcast on television and digital platforms. The analysis reveals that the Frisian Flag advertisement conveys a central message about the importance of energy in supporting youth activities, utilizing dynamic visuals, coherent narratives, and memorable slogans. The advertisement functions not only as a promotional tool but also as a medium for delivering social messages that influence consumer perceptions and behavior. Thus, this study contributes to understanding the strategic role of advertisements in shaping public opinion through hidden discourse.